Dietary Intake of Vitamin D in Young University Students from Leicester, England - Antonio Peña-Fernández; Edna Segura; María de los Ángeles Peña; Manuel Higueras (Biology and Life Sciences Forum, 2023)
About 30–40% of the general population in the United Kingdom (UK) has been reported to have vitamin D deficiency during winter months, representing a public health risk. The aim of this study was to assess the dietary intake of vitamin D in university students at De Montfort University (DMU, UK). Nutrient intake data were collected from 111 (20.45 yrs old; 78 female) DMU students (41 Asian, 41 African and 27 European; 2 unclassified). The dietary intake of vitamin D was slightly higher in male participants (4.287 vs. 3.853 µg/day; p-value = 0.196), which could be attributed to the generally higher intake of food products rich in this vitamin, specifically cereals (436.165 vs. 308.750 g/day; p-value = 0.002), meat (271.553 vs. 193.063 g/day; p-value = 0.016) and bacon (4.911 vs. 1.551 g/day; p-value = 0.024), intakes of which were significantly higher in males. The dietary intakes of vitamin D recorded are lower than the amount of 10 µg/day recommended by the UK’s National Health Service. Intake did not show statistical differences according to ethnic background (Asian (3.708) < African (4.109) < European (4.199); all in µg/day), which might reflect poor and similar dietary habit/choices when students transition from home to university regardless of ethnic background. Our results suggest some prevalence of hypovitaminosis D in DMU students which should be tackled to prevent diseases related to vitamin D deficiency.